Estimating the growth effects of services sector: A cointegration analysis for Pakistan - Abdul Jalil; Samia Manan; Sundus Saleemi (Journal of Economic Structures, 2016)
This article empirically tests the hypothesis of Pugno (Struct Change Econ Dyn 17:99-115, 2006) that both business- and household-related services contribute in the economic growth of the country in the case of Pakistan over the period of 1960-2014. To accomplish the task, the study uses Johansen-Juselius cointegration test and autoregressive distributed lag bounds test to test the long-run relationship between the services sector and the economic growth of Pakistan. The tests reveal that the services sector has a long-run relationship with the economic growth of Pakistan. Furthermore, the estimation of cointegrating vector shows that the services sector positively contributes in the economic growth of Pakistan.
Keywords: 330; Services sector; Economic growth; Pakistan; ARDL